2023
DOI: 10.3390/medicina59020412
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Syndrome: An Ophthalmic Pathology of the Modern Era

Abstract: Digital device usage has increased significantly in last decade among all age groups, both for educational and recreational purposes. Computer vision syndrome (CVS), also known as digital eye strain (DES), represents a range of ocular, musculoskeletal, and behavioral conditions caused by prolonged use of devices with digital screens. This paper reviews the principal environmental, ocular, and musculoskeletal causes for this condition. Due to the high prevalence of DES and frequent usage of digital devices, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
0
6
0
2
Order By: Relevance
“…Computer Vision Syndrome (CVS), or digital eye strain, is a set of visual and ocular symptoms that affect people who use electronic devices (ED) for extended periods [ 1 ]. These devices include computers, laptops, tablets, e-readers, and smartphones [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer Vision Syndrome (CVS), or digital eye strain, is a set of visual and ocular symptoms that affect people who use electronic devices (ED) for extended periods [ 1 ]. These devices include computers, laptops, tablets, e-readers, and smartphones [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the past two decades, CVS has become a highly relevant health problem that affects the entire population [ 1 ]. A systematic review and meta-analysis study found that the pooled prevalence of CVS is 66% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those with more severe symptoms or higher visual demands may even experience difficulty concentrating or headaches. The symptoms of binocular vision dysfunction above are very similar to CVS and dry eye 5 , 6 ; thus, the mutual influence among CVS, dry eye, and binocular visual functions has also made the diagnostic process more complex in many clinical cases 16 20 . High-tech engineers may experience more severe dry eye and CVS symptoms due to prolonged and specific computer use.…”
Section: Introductionmentioning
confidence: 99%
“…Those with more severe symptoms or higher visual demands may even experience di culty concentrating or headaches. The symptoms of binocular vision dysfunction above are very similar to CVS and dry eye [5][6] ; thus, the mutual in uence among CVS, dry eye, and binocular visual functions has also made the diagnostic process more complex in many clinical cases [19][20] . High-tech engineers may experience more severe dry eye and CVS symptoms due to prolonged and speci c computer use.…”
Section: Introductionmentioning
confidence: 99%